Experimental Investigation of Convection Heat Transfer Enhancement in Horizontal Channel Provided with Metal Foam Blocks (Journal of Engineering, 2016)
Convection heat transfer in a horizontal channel provided with metal foam blocks of two numbers of pores per unit of length (10 and 40 PPI) and partially heated at a constant heat flux is experimentally investigated with air as the working fluid. A series of experiments have been carried out under steady state condition. The experimental investigations cover the Reynolds number range from 638 to 2168, heat fluxes varied from 453 to 4462 W/m2, and Darcy number 1.77x10-5, 3.95x10-6. The measured data were collected and analyzed. Results show that the wall temperatures at each heated section are affected by the imposed heat flux variation, Darcy number, and Reynolds number variation. The variations of the local heat transfer coefficient and the mean Nusselt number are presented and analyzed. The mean Nusselt number enhancement was found to be more than 80% for all the studied cases.